URGENSI FILSAFAT PENDIDIKAN DALAM PEMBELAJARAN BAHASA - Mizkat, Eva; Zaim, M.; Thahar, Harris Effendi (Bahasa Indonesia Prima, 2024)
This research discusses the importance of educational philosophy in the context of language learning. It is considered a theoretical foundation that plays a central role in guiding the goals and methodologies of language learning. By exploring its role in formulating the goals of language education, guiding teaching methods, and creating a conducive learning environment, this research reveals the urgency of educational philosophy in shaping meaningful language learning experiences. The results of this study reveal that the importance of understanding the urgency of educational philosophy in language learning is the first step to creating a better and sustainable educational future. Therefore, educators, researchers, and educational policymakers are urged to pay attention to and consider the philosophical basis in every language learning policy and practice.